Advances in the development of dielectric elastomer generators for wave energy conversion. (January 2020) - Moretti, Giacomo; Santos Herran, Miguel; Forehand, David; Alves, Marco; Jeffrey, Henry; Vertechy, Rocco; Fontana, Marco
Abstract: This paper presents a summary of recent progress towards the development and upscaling of an emerging class of electrostatic power take-off (PTO) systems for wave energy converters (WECs), called dielectric elastomer generators (DEGs). DEGs are electromechanical devices able to convert mechanical energy into electrical energy by exploiting the deformation of rubber-like dielectric materials. The high power density (in the order of hundreds of Watts per kilogram), good efficiency and ease of assembling, combined with the low-cost of the employed materials (a few euros per kilogram) and their intrinsic resilient/reliable response to mechanical shocks make DEGs a very promising option for the deployment of a future generation of WECs. In the last decade, some specific concepts of WECs based on DEGs have been devised and a considerable interest in the topic has been aroused in the wave energy community. Among the candidate DEG topologies for wave energy harvesting, recent studies have suggested that a specific layout, namely the axial-symmetric inflating DEG diaphragm, could be a very promising candidate for future upscaling. This paper first describes the operating principle of DEG PTOs and the effect of electro-mechanical material parameters on their energetic performance. With reference to the above-mentioned inflating DEG diaphragm topology, an overview of concepts for integration on WECs is then provided, with a special focus on advanced concepts enabling the achievement of dynamical tuning with the incoming waves. A general lumped-parameter modelling approach for the design of DEG-based WECs is proposed. Experimental activity carried out to date, i.e. dry-run laboratory tests, wave-tank tests and preliminary sea trials is reviewed, with the aim of showing the progression in the device's scale and performance. Finally, economical and technological considerations are outlined, in order to point out challenges, future research opportunities and to draft a roadmap for future research and technological transfer. Highlights: Recent advances on polymeric power take-off systems for wave energy converters called dielectric elastomer generators (DEGs). Identification of a DEG layout suitable for oscillating water column and pressure differential wave energy converters (WECs). General modelling framework for coupled DEG-WEC systems. Review of experimental testing of scaled prototypes. Roadmap and techno-economic considerations on the future development of WECs based on DEGs.